Respuesta :

Solution :

  • 4x + 6y = - 10
  • 2( 2x + 3y) = - 10
  • 2x + 3y = - 5
  • 2x = - 5 - 3y
  • x = (-5-3y)/2______Equation 1

  • 8x + 10y = - 26
  • 2( 4x + 5y) = - 26
  • 4x + 5y = - 13_____Equation 2

Now by using equation 1 in equation 2 we get,

[tex]4x + 5y = - 13 \\ \\ 4( \frac{ - 5 - 3y}{2} ) + 5y = - 13 \\ \\ \frac{ - 20 - 12y}{2} + 5y = - 13 \\ \\ \frac{ - 20 - 12y + 10y}{2} = - 13 \\ \\ - 20 - 2y = - 26 \\ \\ - 2y = - 26 + 20 \\ \\ - 2y = - 6 \\ \\ y = 3[/tex]

Now upon using the value of y in equation 1, we get

[tex]x = \frac{ - 5 - 3y}{2} \\ \\ x = \frac{ - 5 - 3 \times 3}{2} \\ \\ x = \frac{ - 5 - 9}{2} \\ \\ x = \frac{ - 14}{2} = - 7[/tex]

The answer is
Y=-3
X=2
Ver imagen AnnaChen